Development of brain mechanisms for visual global processing and object segmentation. - Braddick, O; Atkinson, J (2007)
Objects have specific cognitive attributes, elicit particular visuo-motor responses, and require visual processes beyond primary visual cortex to combine information over extended regions as a basis for the segmentation and integration of visual objects. As well as segmentation, the assignment of region boundaries to differentiate figure from ground is a key process whose operation can be observed in infants during the early months. Global organization of both motion and pattern information plays a role in object segmentation and integration. These two types of global processing are associated with different brain systems, have different developmental courses, and are differentially vulnerable in developmental disorders. In infancy, specific visual attributes determine the selection of a manual response (reach-and-grasp vs. surface exploration) and also the detailed kinematic parameters of each class of response. These are taken to reflect the properties of distinct visuo-motor modules whose properties emerge between 4 and 12 months of age. While these modules are a component of the dorsal cortical stream, they must interact with ventral stream processing in development and in the mature system.